Augmenting farmers’ income through Integrated Farming System Model under Farmer FIRST Programme - Arora, R K; Sharma, Pawan Kumar; Kumar, Parveen; Singh, Rajbir (Indian Farming, 2021)
Demonstration of the Integrated Farming System model in an area of 0.5 ha in rainfed (Kandi) villages is one of the essential modules assumed under the Farmer FIRST Programme of SKUAST-Jammu. The model consists of enterprises such as crop, livestock, mushroom and vermicompost etc. with diverse coverage of land area. There was an additional generation of net income of ` 1.61 lakhs from an area of 0.5 ha under the IFS model as compared to the existing farming system. Besides, 130 additional employment days were also generated under IFS model demonstrated under the Farmer FIRST Programme.